The communication of melancholy, grief, and fear in dance with and without music - A. Warrenburg, Lindsay; Reymore, Lindsey; Shanahan, Daniel (Human Technology, 2020)
Professional dancers were video recorded dancing with the intention of expressing melancholy, grief, or fear. We used these recordings as stimuli in two studies designed to investigate the perception and sociality of melancholy, grief, and fear expressions during unimodal (dancing in silence) and multimodal (dancing to music) conditions. In Study 1, viewers rated their perceptions of social connection among the dancers in these videos. In Study 2, the same videos were coded for the amount of time that dancers spent in physical contact. Results revealed that dancers expressing grief and fear exhibited more social interactions than dancers expressing melancholy. Combined with the findings of Warrenburg (2020b, 2020c), results support the idea that—in an artistic context—grief and fear are expressed with overt emotional displays, whereas melancholy is expressed with covert emotional displays.